Advances in Assessment and Modeling of Earthquake Loss - Akkar, Sinan; Ilki, Alper; Goksu, Caglar; Erdik, Mustafa (Springer Tracts in Civil Engineering, 2021)
This open access book originates from an international workshop organized by Turkish Natural Catastrophe Insurance Pool (TCIP) in November 2019 that gathered renown researchers from academia, representatives of leading international reinsurance and modeling companies as well as government agencies responsible of insurance pricing in Turkey. The book includes chapters related to post-earthquake damage assessment, the state-of-art and novel earthquake loss modeling, their implementation and implication in insurance pricing at national, regional and global levels, and the role of earthquake insurance in building resilient societies and fire following earthquakes. The rich context encompassed in the book makes it a valuable tool not only for professionals and researchers dealing with earthquake loss modeling but also for practitioners in the insurance and reinsurance industry.